Morális dilemmák a veszélyek kivédését és szűkös erőforrások elosztását illetően - Baranyi , Ákos (Kultúratudományi Szemle, 2022)
Moral dilemmas regarding the prevention of threats and the allocation of scarce resources Ákos Baranyi The notion of equal treatment lies at the heart of ethics and legal philosophy. Despite the fundamental role that it occupies in ethical and legal theory, it is not that simple as it may seem, the concept of equality is subject to many different interpretations. These approaches are diverging and subjective, but choosing between them is a constitutive element of a principled decision making.